Visitation Enablers and Barriers: Evaluating the Influences of Practical, Relational, and Experiential Factors on Visitation in Dutch Prisons - Berghuis, Maria (Crime & delinquency, 2022)
This paper aims to advance theory and knowledge about prison visitation by organizing prior studies within a framework of visitation enablers and barriers and examining how practical, relational, and experiential factors explain variation in prison visiting among 773 adult males across eight Dutch prisons. Findings suggest that all three domains play out at once to influence visitation. Whether visitors come to visit seems to depend on their relationship with the incarcerated individual, whereas traveling distance is more predictive of how often they visit. Policies that introduce practical barriers can differentially affect visits from specific relationships. Finally, results indicate that incarcerated individuals make decisions about visits based on their in-prison experiences. Policy and research implications are discussed.